Changes in the diagnosis of glomerular diseases in east China: a 15-year renal biopsy study. (15th October 2018) - Zhou, Qin; Yang, Xin; Wang, Meifang; Wang, Huiping; Zhao, Jie; Bi, Yan; Wang, Xiayue; Yao, Jihong; Chen, Ying; Lin, Chuan; Xie, Xishao; Jiang, Hong; et al.
Abstract: Background: There have been some gradual changes in the distribution of renal biopsy pathological diagnoses during recent years. This study aimed to show changes in renal disease prevalence in China by investigating 10 patients diagnosed at our Kidney Disease Centre during the last 15 years. Methods and results: All patients aged 15-year-old or older who underwent renal biopsy at the First Affiliated Hospital, Zhejiang University, from 2001 to 2015 were enrolled. There were 5 common types of primary glomerulonephritis: IgA nephropathy (IgA N), membranous nephropathy (MN), mesangial progressive glomerulonephritis (MsPGN), minimal change disease (MCD), and focal segmental glomerulosclerosis (FSGS), which represented 50%, 16.8%, 15.9%, 8.1% and 2.5% of total cases, respectively. IgA nephropathy was the most common type of primary glomerulonephritis (PGN). Conclusions: Our results mostly showed a new trend that the diagnosis of IgA nephropathy was not increasing and the prevalence of membranous nephropathy had increased, becoming the second most common type of primary glomerulonephritis. Key POINTS: Distinguished with other domestic studies, IgA nephropathy did not show a trend of continuous growth although it still had about the half proportion of PGN, whereas membranous nephropathy kept rising and became the second common PGN. Concerning SGN, LN peaked in the younger-age and middle-age groups with a significant female prevalence, DN, BANS and SV had a male predominance peaking in the middle-age and old-age groups.